Formulation study of PLGA in situ films for topical delivery of salicylates - Snejdrova, Eva; Loskot, Jan; Veris, Andrea; Kastner, Petr; Andrys, Rudolf (European journal of pharmaceutics and biopharmaceutics, 2024)
A film-forming system (FFS) represents a convenient topical dosage form for drug delivery. In this study, a non-commercial poly(lactic-co-glycolic acid) (PLGA) was chosen to formulate an FFS containing salicylic acid (SA) and methyl salicylate (MS). This unique combination is advantageous from a therapeutic point of view, as it enabled modified salicylate release. It is beneficial from a technological perspective too, because it improved thermal, rheological, and adhesive properties of the in situ film. DSC revealed complete dissolution of SA and good miscibility of MS with the polymer. MS also ensures optimal viscoelastic and adhesive properties of the film, leading to prolonged and sustained drug release. The hydrolysis of MS to active SA was very slow at skin pH 5.5, but it apparently occurred at physiological pH 7.4. The film structure is homogeneous without cracks, unlike some commercial preparations. The dissolution study of salicylates revealed different courses in their release and the influence of MS concentration in the film. The formulated PLGA-based FFS containing 5 % SA and 10 % MS is promising for sustained and prolonged local delivery of salicylates, used mainly for keratolytic and anti-inflammatory actions and pain relief.
Keywords: Delayed-Action Preparations; kyselina salicylová; kyselina mléčná; koncentrace vodíkových iontů; farmaceutická chemie; kyselina polyglykolová; Lactic Acid; lékové transportní systémy; Polylactic Acid-Polyglycolic Acid Copolymer; Salicylic Acid; Salicylates; aplikace kožní; Chemistry, Pharmaceutical; léky s prodlouženým účinkem; Hydrogen-Ion Concentration; Skin; aplikace lokální; Drug Liberation; uvolňování léčiv; Solubility; Drug Delivery Systems; salicylany; Polyglycolic Acid; rozpustnost; Administration, Cutaneous; kůže; Administration, Topical; kopolymer kyseliny glykolové a mléčné